2020
DOI: 10.1021/acschemneuro.0c00623
|View full text |Cite|
|
Sign up to set email alerts
|

Contribution of the P2X4 Receptor in Rat Hippocampus to the Comorbidity of Chronic Pain and Depression

Abstract: The hippocampus is an important region for the interaction between depression and pain. Studies show that the P2X4 receptor plays key role in neuropathic pain. This work investigated the potential implication of the P2X4 receptor in the hippocampus in comorbidity of chronic pain and depression. The rat model induced by chronic constriction injury (CCI) plus unpredictable chronic mild stress (UCMS) was used in this study. Our data showed that CCI plus UCMS treatment resulted in abnormal changes in pain and depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Subcortical structures including the hippocampus and basal ganglia have been implicated in chronic pain [ 52 ]. The hippocampus is a key region for memory and learning, which are important aspects of chronic pain and depression [ 53 ] and relevant to their co-occurrence [ 53 , 54 ]. TN patients have been reported to exhibit higher depression and anxiety scores than HCs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subcortical structures including the hippocampus and basal ganglia have been implicated in chronic pain [ 52 ]. The hippocampus is a key region for memory and learning, which are important aspects of chronic pain and depression [ 53 ] and relevant to their co-occurrence [ 53 , 54 ]. TN patients have been reported to exhibit higher depression and anxiety scores than HCs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DEGs were mainly distributed in tissues of the circulatory system, immune system, and neurologic system, consistent with the fact that MDD patients usually Frontiers in Psychiatry 10 frontiersin.org harbor coronary artery disease (29). In our study, the most typical tissues were cardiomyocytes, lymphoma Burkitt, CD33+ myeloid, pineal, and Dorsal Root Ganglion, which might imply the probable reasons for clinical manifestations in MDD, such as repeated infection, circadian rhythm disorder and feeling pain (30,31).…”
Section: Discussionmentioning
confidence: 61%
“…The mechanism by which P2X4 activation after surgery causes PND is unclear. Recent studies have shown the activation of P2X4-mediated NLRP3 inflammasome signaling in multiple models [32], including the hippocampus of rats with comorbidities of chronic pain and depression [33]. Emerging evidence has shown that NLRP3 inflammasome is closely related to the neuroinflammation of postoperative cognitive dysfunction [34].…”
Section: Discussionmentioning
confidence: 99%